Estudos químicos, moleculares, microbiológicos e toxicológicos de novas moléculas eficazes contra biofilmes de pseudomonas aeruginosa e micobactérias de crescimento rápido - Siqueira, Fallon dos Santos (2021)
It is known that microbial infections caused by microorganisms in sessile form are a more challenging issue, with regard to pathogenesis and treatment, than infections caused by planktonic microorganisms. Biofilm maturation and dispersion involves complex mechanisms, influenced by genetic and environmental stimuli. Mycobacterial biofilms contain a cell wall rich in free mycolic acids, which houses bacterial populations, providing greater resistance of this structure to anti-mycobacterial drugs, even when exposed to high concentrations. In addition, pathogenic species such as Pseudomonas aeruginosa and species in the Rapidly Growing Mycobacteria (RGM) group are now showing intense cellular communication mediated by signaling molecules, coupling the transcription of specific genes with bacterial cell density. This process is known as quorum sensing (QS) and induces the growth and three-dimensional grouping of bacteria, provides an increase in the adhesion of the structure to the surface and the formation of aqueous channels for the exchange of water and nutrients with the external environment. he present study aims to contribute to the elucidation and better understanding of the mechanisms involved in virulence and resistance associated with the formation of P. aeruginosa and RGM biofilms, as well as assisting in the search for new therapeutic options for the prevention and eradication of infections associated with the formation of biofilms microbial. In recent years, the derivation of classic antimicrobials has demonstrated excellent activity against a variety of microorganisms, thus stimulating the development of organic and inorganic compounds through different methods of chemical synthesis. To evaluate the biological activities of sulfamethoxazole derivatives, in vitro bacterial growth inhibition assays were used, both in planktonic and biofilm form. Furthermore, in silico molecular docking assays and in vitro QS inhibition assays were performed to suggest the mechanism of action of these molecules. The action of the compounds was observed through Atomic Force Microscopy and the safety profile determined in a model of peripheral blood mononuclear cells (PBMC), through in vitro colorimetric and fluorimetric assays. The results obtained in this work indicated potential antimicrobial activity of sulfamethoxazole silver complexes, as well as promising antibiofilm activity through the inhibition of QS. The compound has been shown to act on the las and Pqs systems, the main regulators of biofilm formation in P. aeruginosa. In addition, an unprecedented Schiff's Base derived from sulfamethoxazole was synthesized and characterized, demonstrating potential antimicrobial and antibiofilm activity against RGM. The two molecules were safe in peripheral blood monocucleated cells. The safety profiles data were obtained through cytotoxic, genotoxic and nitrosative and oxidative modulation tests.